2006
DOI: 10.1158/1078-0432.ccr-06-0953
|View full text |Cite
|
Sign up to set email alerts
|

Photofrin Uptake in the Tumor and Normal Tissues of Patients Receiving Intraperitoneal Photodynamic Therapy

Abstract: Purpose: A phase II trial of Photofrin-mediated i.p. photodynamic therapy shown in a previous report limited efficacy and significant acute, but not chronic, toxicity. A secondary aim of this trial and the subject of this report is to determine Photofrin uptake in tumor and normal tissues. Experimental Design: Patients received Photofrin, 2.5 mg/kg, i.v., 48 hours before debulking surgery. Photofrin uptake was measured by spectroflurometric analysis of drug extracted from tumor and normal tissues removed at su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 21 publications
2
55
0
4
Order By: Relevance
“…The present study, which used an extraction method to quantify the porfimer sodium in mucosal biopsy samples, reports a 10-fold variability in esophageal uptake of porfimer sodium. A similar wide variability among patients in porfimer sodium concentration has been reported in previous studies of other tissues (17,21). Perhaps related to the limited number of patients in this study, this variation in the porfimer sodium tissue content in itself was not shown to be predictive of treatment outcome.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The present study, which used an extraction method to quantify the porfimer sodium in mucosal biopsy samples, reports a 10-fold variability in esophageal uptake of porfimer sodium. A similar wide variability among patients in porfimer sodium concentration has been reported in previous studies of other tissues (17,21). Perhaps related to the limited number of patients in this study, this variation in the porfimer sodium tissue content in itself was not shown to be predictive of treatment outcome.…”
Section: Discussionsupporting
confidence: 82%
“…Holmer et al (15) measured the optical properties of normal, Barrett's, and cancer tissue for modeling of light flux and absorption throughout the esophagus during PDT. Improved tissue characterization and more accurate determination of optical properties are critically important for mathematical modeling and Monte Carlo simulations of optimal PDT dosimetry for PDT light dosimetry planning (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Technical issues and normal tissue toxicities currently preclude the broader applicability of PDT for the treatment of invasive malignancies (4,11,12). The use of PDT in these settings has been associated with a narrow therapeutic index and recurrent disease is common.…”
Section: In This Issue Of Clinical Cancer Research Kabingu and Collementioning
confidence: 99%
“…It involves administration of a photosensitizing drug followed by the application of a specific wavelength of light, leading to intracellular photoexcitation and injury (11). Theoretically, PDT can cure gastrointestinal neoplasms contained within the submucosal layer (10,12,13). It is a highly effective, painless, and usually well-tolerated procedure that is simple to perform (10,13).…”
Section: Introductionmentioning
confidence: 99%